Corporate Governance and Financial Statement Fraud in the Nigerian Oil and Gas Sector - Osemwegie-Ero , Joy Omeghie.; Jackson-Akhigbe , Beauty E.; Osagie-Oyegue, Joy (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The study examined corporate governance characteristics and financial statement fraud in Nigerian oil and gas corporations has been explored in this study. In order to emphasize the conflicting results in the literature, the empirical review examines earlier research works on corporate governance and financial statement fraud. The study uses secondary data extracted from the annual reports of nine (9) oil and gas companies listed on the Nigeria exchange group from 2012 to 2021. To determine the possibility of financial statement fraud, the technique uses panel least squares analysis while the Beneish M-score model was used to measure financial statement fraud. The results demonstrate that board gender diversity and board audit committee do not significantly affect financial statement fraud, whereas board financial expertise and audit committee do. The study recommends the importance of corporate governance in preventing financial statement fraud as well as suggestions for putting into place effective governance mechanisms, coordinating incentives, enhancing transparency, and promoting an ethical workplace culture.